PENGEMBANGAN EKOWISATA DI PULAU PENYU TANJUNG BENOA BALI BERDASARKAN PRINSIP-PRINSIP EKOWISATA - I Putu Oka Saduarsa; I Gusti Ngurah Putra Dirgayusa; Ni Luh Putu Ria Puspitha (Fakultas Kelautan dan Perikanan Universitas Udayana, 2022)
The existence of sea turtle in its habitat, especially in Bali is endangered. Moon cot sari sea turtle island is a one of tourist destination that carries out conservation of sea turtles. This turtle island provides more education about turtles to the tourists. Turtle island is still in the developing stage to become an ecotourism destination. Ecotourism defines as a tourism that emphasizes the responsibility of preserving nature, providing economic benefits and maintaining cultural integrity for the local community. The development of turtle island as an ecotourism destination could be evaluated from the implementation of the principles of ecotourism such as education, recreation, society walfare, pasticipation of society. The data was collected using interview by closed question questionnaire and the output of this research is a descriptive value. The questionnaire were used to asses if those principles were already applied in turtle island or not. The total of respondents 450 tourists, 15 person staff and 15 person local community. Sampling is carried out for 1.5 months from January to March 2019 every Sunday according to the high season period on that month. The results found that on average 80% of respondents answered that they have gained insight about sea turtles and better understand about sea turtles conservation (principle of education), 75.5% of respondents answered that the turtle island has adequate facilities to give the impression of a pleasant tour (principle of tourism), 100% of staff and stakeholder respondents said the turtle island had a better economic impact (society walfare), 100% of the society respondents said that they participated in preserving the turtle and the environment of the local mangrove forest ( principle of society participation and conservation).